Inequality and savings - Henrik Yde Andersen; Thomas Krause; Alina Kristin Bartscher; Andreas Kuchler (Danmarks Nationalbank, 2022)
This memo studies the impact of demographic shifts and income inequality on the evolution of savings rates in Denmark, and compares with evidence from the US. Income inequality has followed similar trends in Denmark as in the US, and savings rates vary in a similar way over the life cycle and along the income distribution in the two countries. Changes in savings behavior play an important role for the evolution of total savings.
Keywords: 330; Einkommensverteilung; Bevölkerungsentwicklung; Sparen; Lebensverlauf; Vergleich; Dänemark; USA